Implementasi QR Code Untuk Sistem Informasi Pemesanan Menu Pada Restoran Omah Gedhe Pandean Kaliwungu Berbasis Web - Rusito, Rusito; Diyah Intan Mawarni Putri (LogicLink, 2024)
This study aims to develop and implement a web-based menu ordering information system using QR Codes at Omah Gedhe Pandean Kaliwungu Restaurant. The system is designed to enhance efficiency and convenience in the food ordering process at the restaurant. QR Codes are used as a medium to access the digital menu, allowing customers to scan the codes with their mobile devices to directly view the menu and place orders without waiting for a waiter. The results of this implementation show that the QR Code-based information system can improve service speed, reduce ordering errors, and provide a more interactive experience for customers. This research employs the Research and Development (R&D) method by Brog & Gall, which is used to produce and test specific products. The study uses 6 out of the 10 steps of this method. Validation results from experts and users show an average validation score of 31.5 from 2 respondents, which falls within the 31-40 range on the value indicator table, leading to the conclusion that the system design is "Highly Valid."